2013
DOI: 10.5301/ejo.5000256
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Nasolacrimal Duct Obstruction: Clinical Profile, Management, and Outcome

Abstract: Naso-orbito-ethmoidal fracture is the main cause of traumatic NLDO, commonly in young male individuals. Telecanthus is an important presenting feature. Computed tomography-dacryocystography is a useful imaging modality in preoperative assessment and surgical planning. External dacryocystorhinostomy with or without intubation under general anesthesia gives good surgical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Naso-orbitoethmoid fractures are the leading cause of noniatrogenic etiology. Mukherjee and Dhobekar (5) reported that 18 out of 28 cases (64%) were associated with bony fractures. In our study, 19 out of 40 eyes (47.5%) with traumatic NLDO were associated with NOE fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Naso-orbitoethmoid fractures are the leading cause of noniatrogenic etiology. Mukherjee and Dhobekar (5) reported that 18 out of 28 cases (64%) were associated with bony fractures. In our study, 19 out of 40 eyes (47.5%) with traumatic NLDO were associated with NOE fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Iatrogenic damage to the lacrimal drainage system usually associated with paranasal sinus and rhinoplastic surgeries is another major cause of traumatic NLDO (4). Reassessment of the NLDO should be performed 1 to 3 months after initial trauma when resolution of edema and soft tissue injuries permits definitive evaluation (5). Careful assessment, including the level of obstruction, is critical for medical decision-making and outcome (2).…”
Section: Introductionmentioning
confidence: 99%
“…Of those 27, 10 were found to have normal patency of the lacrimal system and there was spontaneous resolution of the epiphora in all patients within 5 months posttrauma; the other 17 patients underwent external dacryocystorhinostomy (DCR) with a success rate of 94%. 16 There have been excellent results reported using external DCR for the treatment of posttraumatic nasolacrimal obstruction with 92.8% success in Ali et al's cohort with external DCR and mitomycin C and silicone intubation, 12 96% success in Mukherjee and Dhobekar's cohort with external DCR with and without silicone intubation, 19 and Becelli et al's cohort as noted above. 16 The advent of endoscopic DCR has allowed surgeons to treat nasolacrimal duct obstruction without an external scar, with faster postoperative recovery time, and avoidance of injury to the lacrimal pump.…”
Section: Nasolacrimal Duct Obstructionmentioning
confidence: 92%
“…Patients with a Le Fort II fracture and naso-orbito-ethmoidal fractures are at risk. 10 Occasionally, the lacrimal duct is damaged by osteosynthesis material.…”
Section: Lacrimal Ductmentioning
confidence: 99%